RIFM fragrance ingredient safety assessment, 3-phenylpropyl acetate, CAS Registry Number 122-72-5. (May 2022) - Api, A.M.; Belsito, D.; Botelho, D.; Bruze, M.; Burton, G.A.; Cancellieri, M.A.; Chon, H.; Dagli, M.L.; Date, M.; Dekant, W.; Deodhar, C.; Fryer, A.D.; et al.
Highlights: 3-Phenylpropyl acetate; a safety assessment based on RIFM's criteria. A safety assessment based on 7 human health endpoints plus environmental. All endpoints were cleared using target data, read-across, and/or TTC. Abstract : Therefore, the phenethyl formate MOE for the fertility endpoint can be calculated by dividing the phenethyl alcohol NOAEL in mg/kg/day by the total systemic exposure to phenethyl formate, 1000/0.00062 or 1612903.